Makna dalam Era Digital: Kajian Semantik terhadap Bahasa di Media Sosial Indonesia - Dian Maharani; Hasea Sabam Simanjuntak; Nailah cahyani; Rowimatul Hazizah; Yuliana sari (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2025)
The development of social media has triggered a dynamic shift in the meaning of language used in everyday communication. This article aims to analyze the lexical meaning changes and expansions in the Indonesian language as used on social media platforms, particularly Twitter and Instagram. This study employs a descriptive semantic approach with content analysis methods applied to selected viral posts. The findings show that many words experience semantic shift, the formation of new meanings (neologisms), and altered connotations based on digital context. These results highlight the importance of semantic understanding in interpreting the evolving nature of language in the digital era.